PENGARUH BUDAYA ORGANISASI DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU - Saputra, R Marwan Indra (Eko dan Bisnis: Riau Economic and Business Review, 2017)
This research is at the Sungai Lala Sub-District Office, Indragiri Hulu Regency. The formulation of the problem is whether the organizational culture and work placement simultaneously affected the employee's performance. The purpose of this study is to determine the effect of organizational culture and work placement simultaneously on employee performance. This study used sampling with the Census Method, which all the population became sample in this research as many as 26 respondents. To analyzed the data, this research used descriptive analysis and quantitative analysis by using Multiple Linear Regression SPSS Software Version 21. Results of Multiple Linear Regression Analysis obtained Y = 1,841 + 1,016X1 + 0,129X2 a = 1,841 it means that if the organizational culture and work placement are equal to 0 (zero) or constant (no increase and decrease) then the magnitude of performance is 1,841 points, b1 = 1.016 it means that if organizational culture increases by 1 (one) unit (while permanent work placement) then performance will increase by 1,016 points, b2 = 0.129 it means tgat if work placement increases by 1 (one) unit (while organizational culture remains) then performance will experience an increase of 0.129 points. The simultaneous test results (F test) obtained the value of Fcount> Ftable, then based on data testing criteria it can be seen that Ha is accepted and H0 is rejected, meaning that organizational culture and work placement together (simultaneous) affect the performance. The results of the calculation of the R test, have a very strong and unidirectional relationship between organizational culture and work placement with performance, meaning that if organizational culture and work placement increases, performance will also increase and R Square values or determination coefficient of 0.647 means that the performance variables can be explained by organizational culture and work placement variables of 64.7%, while the remaining 35.3% are explained by other independent variables not examined.